Comparison of the Postprocedural Quality of Life between Coronary Artery Bypass Graft Surgery and Percutaneous Coronary Intervention: A Systematic Review - Kaneez Fatima; Mohammad Yousuf-ul-Islam; Mehreen Ansari; Faizan Imran Bawany; Muhammad Shahzeb Khan; Akash Khetpal; Neelam Khetpal; Muhammad Nawaz Lashari; Mohammad Hussham Arshad; Raamish Bin Amir; Hoshang Rustom Kakalia; Qaiser Hasan Zaidi; et al. (Cardiology Research and Practice)
The treatment of choice between coronary artery bypass graft surgery (CABG) and percutaneous coronary intervention (PCI) has remained unclear. Considering quality of life (QOL) increases life expectancy, we believe QOL should be important in determining the optimum treatment. Thus the objective of this review was to illustrate the comparative effects of CABG and PCI on postprocedural QOL. Methods. We searched PubMed (Medline) and Embase from inception of the databases to May 2014 using “PCI versus CABG quality of life”, “Percutaneous Coronary intervention versus Coronary artery bypass graft surgery Quality of life”, “PCI versus CABG health status”, “Angioplasty versus CABG”, “Percutaneous coronary intervention versus coronary artery bypass surgery health status”, and different combinations of the above terms. 447 articles were found. After applying strict exclusion criteria, we included 13 studies in this review. Results. From the 9 studies that compared QOL scores at 6 months after procedure, 5 studies reported CABG to be superior. From the 10 studies that compared QOL among patients at 1 year after procedure, 9 reported CABG to be superior. Conclusion. It can be established that CABG is superior to PCI in improving patient’s QOL with respect to all scales used to determine quality of life.